Superhydrophobicity of Kapok Fiber and It Performance in Oily Water - HAMIDON, MUHAMMAD ADAM BUKHORI; Hussin, Rosniza (Progress in Engineering Application and Technology, 2021)
Kapok fiber is a normally inexhaustible material with enormous lumen and hydrophobic attributes, which empowers it to show great oil sorption limit. The main objective of this study is to characterized physical properties of kapok fiber, analyze super hydrophobicity properties of kapok fiber and evaluate the efficiency separation of oil-in-water emulsion using kapok fiber. The results show that the kapok fiber additionally showed high separation effectiveness for oil/water mixtures and can rapidly retain drifting oils on water surface during filtration of the oil/water mixture using kapok fiber as a filtration medium. The discoveries recommend that the attractively super hydrophobic kapok fiber has the possibility of potential applications in the expulsion and recuperation of spilled oil toxin, implying excellent recyclability in the oil sorption.